The relationship between macroeconomic factors towards economic growth in Malaysia / Ainul Syazana Mohamad Hamidi and Nur Nadzirah Zulkifili - Mohamad Hamidi, Ainul Syazana; Zulkifili, Nur Nadzirah (Faculty of Business Management, 2016)
This paper studies the relationship between foreign direct investment, inflation rate, export and exchange rate on economic growth in Malaysia during the period from 1984-2014. All the variables seem to have relationship with economic growth. Unit root test and diagnostic test were being used to test whether it is stationary or non-stationary. The analyses are conducted using multiple linear regression to get the results. Foreign direct investment and export show a positively relationship towards economic growth, therefore, it is perfectly significant. The multiple linear regression results show that all the independent variables were significant relationship towards dependent relationship since the F-value and P-value were 8.428080 and 0.000169 respectively. The null hypothesis has been rejected because the F-statistic is statistically significant at 1% significant level. Based on the result, exchange rate is the most factors that give impact on economic growth.